2013
DOI: 10.1103/physrevlett.110.151803
|View full text |Cite
|
Sign up to set email alerts
|

First Observation of the DecayBs2*(5840)0B*+

Abstract: The properties of the orbitally excited (L ¼ 1) B 0 s states are studied by using 1:0 fb À1 of pp collisions at ffiffi ffi s p ¼ 7 TeV collected with the LHCb detector. The first observation of the B Ã s2 ð5840Þ 0 meson decaying to B Ãþ K À is reported, and the corresponding branching fraction measured relative to the B þ K À decay mode. The B s1 ð5830Þ 0 ! B Ãþ K À decay is observed as well. The width of the B Ã s2 ð5840Þ 0 state is measured for the first time, and the masses of the two states are determined … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 24 publications
9
28
0
Order By: Relevance
“…[5]. These authors determined the spectrum of B s 1P states and they found that the masses of B s1 (5830) 0 and B * s2 (5840) 0 agree very well with the experimental results [1][2][3][4]. They predicted also the existence of the spin zero positive parity state (J P = 0 + ) with the mass m B s0 = 5.711(13) (19) [10][11][12][22][23][24].…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…[5]. These authors determined the spectrum of B s 1P states and they found that the masses of B s1 (5830) 0 and B * s2 (5840) 0 agree very well with the experimental results [1][2][3][4]. They predicted also the existence of the spin zero positive parity state (J P = 0 + ) with the mass m B s0 = 5.711(13) (19) [10][11][12][22][23][24].…”
Section: Introductionsupporting
confidence: 68%
“…Two positive parity mesons B s states: the J P = 1 + state B s1 (5830) 0 and the J P = 2 + state B * s2 (5840) 0 were observed by the CDF and LHCb collaborations [1][2][3][4]. Recent lattice results [5,6], as well as other work [7][8][9][10][11][12][13][14][15], have indicated that the observed states are most likely members of the (1 + , 2 + ) doublet.…”
Section: Introductionmentioning
confidence: 92%
“…While the so-called exotic states not conforming to quark model states have received the bulk of the attention [2][3][4][5][6], states that appear to be conventional quark model states can provide a useful test of the continued utility of the quark model [7][8][9]. Over the last decade the D0 [10,11], CDF [12][13][14], LHCb [15,16] and CMS [17] hadron collider experiments have observed a number of excited bottom and bottom-strange mesons. We summarize the properties of these states in Table I where we quote the Particle Data Group (PDG) values, averaged over charge states [18].…”
Section: Introductionmentioning
confidence: 99%
“…Orbitally excited states of the B 0 s meson were observed by the CDF and D0 Collaborations via the decays into B ( * )+ K − [3,4]. More recently, the LHCb Collaboration presented a more precise study of these states and observed the decay B * s2 (5840) 0 → B * + K − [5], favouring the spin-parity assignment J P = 2 + for the B * s2 (5840) 0 state. The CDF Collaboration subsequently presented a study of excited B meson states [6] that included measurements of the B ( * ) s1,2 → B ( * )+ K − decays.…”
Section: Introductionmentioning
confidence: 99%